2016
DOI: 10.1038/srep25019
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular chromobody delivery by mesoporous silica nanoparticles for antigen targeting and visualization in real time

Abstract: Chromobodies have recently drawn great attention as bioimaging nanotools. They offer high antigen binding specificity and affinity comparable to conventional antibodies, but much smaller size and higher stability. Chromobodies can be used in live cell imaging for specific spatio-temporal visualization of cellular processes. To date, functional application of chromobodies requires lengthy genetic manipulation of the target cell. Here, we develop multifunctional large-pore mesoporous silica nanoparticles (MSNs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 42 publications
1
42
0
1
Order By: Relevance
“…Endosomal rupture is triggered using chloroquine[19] and FRB-VC is released to the cytosol. FRB-VC diffuses to the nucleus and interacts with FKBP-VN, which is primed for dimerization with pre-bound rapamycin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Endosomal rupture is triggered using chloroquine[19] and FRB-VC is released to the cytosol. FRB-VC diffuses to the nucleus and interacts with FKBP-VN, which is primed for dimerization with pre-bound rapamycin.…”
Section: Resultsmentioning
confidence: 99%
“…Large-pore MSNs were surface-functionalized with NTA-Ni complexes (MSN-Ni) through a series of modifications (Figure 2(a)) to accommodate pH dependent binding and release of the His-tagged FRB-VC[10,11,19]. STEM and SEM images (Figure 2(b)) indicated that the resulting nitrilotriacetic acid-modified MSNs (MSN-NTAs) exhibit uniform particle size and coral surface morphology with irregular pore shape (pore size ranging from 10 – 40 nm) consistent with the structure of the un-functionalized form (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dies kann entweder durch Destabilisierung der endosomalen Membran mittels Lipiden oder osmotischen Drucks oder aber durch die Translokation des Biomoleküls durch Transmembranporen erreicht werden . 2016 entwickelten Chiu und Mitarbeiter großporige mesoporöse Siliciumdioxid‐Nanopartikel (MSNs), die mit Nitrilotriessigsäure(NTA)‐Gruppen an der inneren Oberfläche der MSNs funktionalisiert sind (Abbildung d) . Die Aktivierung des Komplexes mit verschiedenen Metallionen ermöglichte die kovalente Bindung eines His 6 ‐markierten GFP‐Chromobody.…”
Section: Einschleusung Von Kleinen Antigenbindenden Proteinen In Zellenunclassified
“…achieved is through antibody-antigen interactions, and indeed, MSN-antibody conjugates have been reported that were used for analyte detection, 14-17 theranostics/imaging, [17][18][19][20][21][22] or cell targeting. [23][24][25][26][27][28] However, these examples demonstrate a specific recognition of an antigen by the MSN-antibody conjugate, but the recognition event itself does not stimulate a signal or killing response, i.e., there is no antigen-responsive gatekeeping mechanism that would selectively control cargo release only in the presence of a specific antigen or pathogen.…”
Section: Introductionmentioning
confidence: 99%